2023
DOI: 10.2196/47114
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Pulmonary Rehabilitation: Comprehensive Review

Abstract: Background Pulmonary rehabilitation is a vital component of comprehensive care for patients with respiratory conditions, such as lung cancer, chronic obstructive pulmonary disease, and asthma, and those recovering from respiratory diseases like COVID-19. It aims to enhance patients’ functional ability and quality of life, and reduce symptoms, such as stress, anxiety, and chronic pain. Virtual reality is a novel technology that offers new opportunities for customized implementation and self-control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…A previous study that is the most similar to ours is the comprehensive review of VR for pulmonary rehabilitation by Pittara et al [ 32 ] in 2023. They offer a broader overview of VR applications in pulmonary rehabilitation by including all types of VR experiences, ranging from nonimmersive to fully immersive, and various populations, including healthy individuals as well as patients with COPD and asthma.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A previous study that is the most similar to ours is the comprehensive review of VR for pulmonary rehabilitation by Pittara et al [ 32 ] in 2023. They offer a broader overview of VR applications in pulmonary rehabilitation by including all types of VR experiences, ranging from nonimmersive to fully immersive, and various populations, including healthy individuals as well as patients with COPD and asthma.…”
Section: Discussionsupporting
confidence: 68%
“…They offer a broader overview of VR applications in pulmonary rehabilitation by including all types of VR experiences, ranging from nonimmersive to fully immersive, and various populations, including healthy individuals as well as patients with COPD and asthma. In comparison to Pittara et al [ 32 ], our review takes a more focused approach by specifically filtering publications to include only immersive VR experiences within pulmonary rehabilitation programs for outpatients. The main strength of our review therefore lies in its clearly defined goals to provide an overview of immersive VR experiences for outpatients experiencing long COVID and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…This initiative presented a collection of mini-games designed to train participants in fundamental breathing skills. These games included popping bubbles with a forceful breath and extinguishing candles with a prolonged breath [68].…”
Section: Versatility Of Vr Applications In Various Healthcare Discipl...mentioning
confidence: 99%
“…Collectively, these studies underscore a range of innovative approaches in utilizing VEs for respiratory exercises. They demonstrate creativity in design and interactivity, emphasizing the potential to enhance breathing awareness and control through diverse and engaging methodologies [68].…”
Section: Versatility Of Vr Applications In Various Healthcare Discipl...mentioning
confidence: 99%
“…However, a previous report documented seven electronic libraries and 32 review studies from 2010 to 2023 from Digital Library, Google Scholar, IEEE Explore, MEDICINE, PubMed, Sage, and ScienceDirect. 54 Therefore, the meaning of this study can be suggested that VR and PR have been studied concerning VR's impact on the quality of life from exercise and pulmonary rehabilitation in humans with chronic lung disease under a controlled study design. Moreover, the validity of the results of the three clusters in this study with the Cosine normalization algorithm can be supported by previous evidence, 33 data visualization from the occurrence matrix, 55 network mapping visualization with Kamada-Kawai layout algorithm, 56, and related to the Walktrap algorithm.…”
Section: Network Clustering and Most Frequency Wordsmentioning
confidence: 99%